1983
DOI: 10.1073/pnas.80.5.1362
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human serum spreading factor with monoclonal antibody.

Abstract: Serum spreading factor is a glycoprotein isolated from human serum that promotes spreading of a variety of cell types on culture dishes. We developed mouse hybridoma lines secreting monoclonal antibody to serum spreading factor that markedly inhibited the rate of serum spreading factor-promoted spreading of both fibroblastic and epithelial cells in culture. Fibronectin-promoted cell spreading was unaffected by monoclonal antibody to serum spreading factor, and the factor appeared to be distinct by several crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(38 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…Vitronectin and other serum proteins that contain RGD sequences have been implicated as the factors to promote cell spreading (23,24). From the data presented in this study, we propose a novel mechanism of the smooth muscle cell spreading in fibrin gel.…”
Section: Figmentioning
confidence: 85%
“…Vitronectin and other serum proteins that contain RGD sequences have been implicated as the factors to promote cell spreading (23,24). From the data presented in this study, we propose a novel mechanism of the smooth muscle cell spreading in fibrin gel.…”
Section: Figmentioning
confidence: 85%
“…Primary cultured SMC expressed the two VN forms at 65 and 75 kd, corresponding to the two well-characterized forms of human VN. 32 Smaller polypeptides were also detected and were thought to be proteolytic fragments. In this respect, it has been reported that VN can be cleaved and degraded by various enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In circulating blood, vitronectin occurs in two molecular forms: a single-chain 75 kDa form (V& and a clipped form composed of two chains (65 kDa and 10 kDa) which are held together by a disulfide bridge (VSS + 10) [2,8,9]. The endogenous proteinase responsible for this cleavage has not been identified, but the cleavage was shown to occur at the Arg3"-Ala3*' bond…”
Section: Introductionmentioning
confidence: 99%